PENGEMBANGAN MODUL DIGITAL SISTEM BAHAN BAKAR INJEKSI PADA MATA KULIAH TEKNOLOGI SEPEDA MOTOR: DEVELOPMENT OF DIGITAL MODULE OF FUEL INJECTION SYSTEM IN MOTORCYCLE TECHNOLOGY COURSE - Aspar Podungge; Hendra Uloli; Sugengn Pramudibyo (Jurnal Pendidikan Teknik Mesin, 2025)
Development of Digital Module of Fuel Injection System in Motorcycle Technology Course. Thesis. Mechanical Engineering Education Study Program, Department of Industrial Engineering, Faculty of Engineering, Gorontalo State University. Under the guidance of Mr. Hendra Uloli, ST., MT and Mr. Sugeng Pramudibyo, S.Pd., M.Pd. This study aims to Develop a Digital Module of Fuel Injection System in Motorcycle Technology Course. Creative and innovative learning media helps students in the learning process. This study is to determine the practicality and attractiveness of the development of Digital Module learning media with the help of the Canva and H5P applications in Motorcycle Technology courses. The method used in this study is research and development with a 4D model with stages (define, design, development, disseminate) involving 35 respondents. The data collection instrument used is a questionnaire. This research was conducted on students of Mechanical Engineering Education, Gorontalo State University. The data analysis technique used is quantitative data analysis, the evaluation data obtained by the validator is analyzed descriptively and qualitatively. From the research results obtained the results of the media expert's validity of 90.66%, the design expert's validity of 94% and the material expert's validity of 89.23% with each aspect categorized as very feasible. Meanwhile, the assessment results from students obtained a percentage of practicality of 89.57% with a very practical category and a percentage of attractiveness of 88.14% which is in the very interesting category.